Epigenetics in plant breeding - Rajnović, Tihana; Vokurka, Aleš; Bolarić, Snježana (Journal of Central European agriculture, 2020)
Current farming technology and advanced techniques of plant breeding are tending to enable high yields and cropping intensity, trying to alleviate the limitations of available arable land. However, rise in global population and climate changes could strain the ability to provide a stable food supply. Genetic diversity, which might be used for development of new, more resilient cultivars, could be a key for achieving better performance in agricultural production. New findings about how genes work and express, including the principles of epigenetics, could allow the advancements in breeding methods, and provide a new source of variability originating from epialleles. This paper provides a synopsis of the most significant epigenetic modifications, and particularities of plant species that impact epigenetic mechanisms, although it is mainly focused on application of epigenetics on plant breeding. Epigenetic aspects of breeding are described for increased yield in Brassica napus due to recursive selection for an epigenetic compound. Future application might be based on epigenetic recombinant inbred lines, similar to those in Arabidopsis thaliana, inhibition of DNA methylation in Oryza sativa, discovery of MSH1 system in Glycine max and Solanum lycopersicon. It also outlines the current issues and limitations of epigenetic breeding such as a lack of understanding of epigenetic mechanisms, interaction of epigenetic and stress responsive mechanisms, and the development of statistical models able to predict the impact and outcome of epigenetic modifications.